2007
DOI: 10.1001/archpedi.161.8.792
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fast Food Branding on Young Children's Taste Preferences

Abstract: Objective: To examine the effects of cumulative, realworld marketing and brand exposures on young children by testing the influence of branding from a heavily marketed source on taste preferences.Design: Experimental study. Children tasted 5 pairs of identical foods and beverages in packaging from McDonald's and matched but unbranded packaging and were asked to indicate if they tasted the same or if one tasted better. Setting: Preschools for low-income children.Participants: Sixty-three children (mean ± SD age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
230
0
18

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 363 publications
(255 citation statements)
references
References 14 publications
7
230
0
18
Order By: Relevance
“…Wardle and Huon (2000) found that children 9-11 years old liked a drink labeled "new drink" more than a drink labeled "new health drink." Robinson et al (2007) found that children 3-5 years old preferred sampled food items that were branded as McDonalds, which they may have perceived as less healthy. The negative effect of health branding found in previous research could be due to preexisting associations between healthy food and less tasty food.…”
Section: Children's Instrumental Eatingmentioning
confidence: 97%
“…Wardle and Huon (2000) found that children 9-11 years old liked a drink labeled "new drink" more than a drink labeled "new health drink." Robinson et al (2007) found that children 3-5 years old preferred sampled food items that were branded as McDonalds, which they may have perceived as less healthy. The negative effect of health branding found in previous research could be due to preexisting associations between healthy food and less tasty food.…”
Section: Children's Instrumental Eatingmentioning
confidence: 97%
“…For advertisements of energydense, nutritionally questionable foods to affect preferences, the viewer must receive the message by paying attention to a medium that delivers this content. 24,25,[40][41][42][43] Food advertising is especially common during the times young people watch TV. 44 Such messages are rarer in video games and computer content, appearing in product placement, immersive advertising environments, and "advergames."…”
Section: Discussionmentioning
confidence: 99%
“…Research in children marketing indicates that young consumers start recognizing brands from an early age [47] and that the product bearing a brand's logo leads to more enthusiasm on their behalf than a no-name product [46]. Furthermore, children readily respond to advertising messages and evaluate them less critically than adults because they have not yet developed the advertising knowledge and cognitive skills necessary to cope effectively with advertising messages [4].…”
Section: Children As Target Customersmentioning
confidence: 99%